Pemanfaatan Teknologi Digital dalam Administrasi Pendidikan di Era Artifical Intelligence (AI) - Dedek Agustianingsih; Miftahir Rizqa; Nabila Azzahra; Septi Dwi ILva; Serly Oktavianti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Abstract:The development of Artificial Intelligence (AI) has brought significant changes to educational administration. This study aims to examine the utilization of digital technology in educational administration in the AI era through a literature review method. The findings indicate that digital technology and AI can improve the effectiveness and efficiency of educational administration through task automation, data management, data-driven decision making, and enhanced communication. However, their implementation still faces several challenges, including limited infrastructure, low digital literacy, data security issues, and budget constraints. Therefore, the development of integrated digital systems, improvement of technological infrastructure, and enhancement of human resource competencies are necessary to support the effective use of AI in educational administration. With proper implementation, AI can contribute to creating a more effective, high-quality, and adaptive educational system. Keywords: Artificial Intelligence (AI), digital technology, educational administration, management information systems, digital transformation. Abstrak Perkembangan Artificial Intelligence (AI) telah membawa perubahan dalam administrasi pendidikan. Penelitian ini bertujuan mengkaji pemanfaatan teknologi digital dalam administrasi pendidikan di era AI melalui metode studi literatur. Hasil kajian menunjukkan bahwa teknologi digital dan AI dapat meningkatkan efektivitas serta efisiensi administrasi melalui otomatisasi pekerjaan, pengelolaan data, pengambilan keputusan berbasis data, dan peningkatan komunikasi. Namun, implementasinya masih menghadapi kendala berupa keterbatasan infrastruktur, rendahnya literasi digital, masalah keamanan data, serta keterbatasan anggaran. Oleh karena itu, diperlukan pengembangan sistem digital yang terintegrasi, peningkatan infrastruktur, dan penguatan kompetensi sumber daya manusia agar AI dapat mendukung terwujudnya pendidikan yang lebih berkualitas dan adaptif terhadap perkembangan teknologi Kata Kunci: Artificial Intelligence (AI), teknologi digital, administrasi pendidikan, sistem informasi manajemen, transformasi digital.